Uji Aktivitas Lakase dan Selulase pada Lignoselulosa Gambut dengan Berbagai Kadar Air - Ronny Mulyawan; Lilik Tri Indriyati; Happy Widiastuti; Supiandi Sabiham (Jurnal Ilmu Pertanian Indonesia, 2019)
The degradation of lignocellulose as the main constituents of peat is catalyzed by enzymes such as laccase or cellulase. The purpose of this research was to study the pattern of laccase and cellulase activities on sterile and non-sterile peat materials at three different water contents (125-175, 225-275, and 325-375%). The peat soil used was collected from oil palm rhizosphere in Riau Province. This research used the descriptive method by comparing the mean values between treatments. The results showed that enzymes activities on sterile and non-sterile peat added with laccase or cellulase were higher compared to those without enzyme addition. The highest laccase activity was at the first day of incubation, while that for selulase was at the 10th days of incubation. The activity of enzyme then decreased with the increase in the respected incubation time. The difference in decreasing of lignin and cellulose content at 125-175% water content was higher than at the other water contents. The decreases in lignin and cellulose contents were higher by addition of respected enzymes both in sterile and non-sterile peat. It could be concluded that at higher water content, laccase and cellulase activities were depressed both on sterile and non sterile peat, especially after the addition of enzyme.